A Suitable Lawful Structure for Introduction of Islamic Banking in India: An Outline - Pandu, A.; Hussain, Mohammed Galib (Indian Journal of Finance, 2012)
This paper examines the Islamic Banking system on a domestic level in comparison to the global level as well as compares the same to the conventional banking system. A well-developed banking system is a pre-requisite for the smooth and effective functioning of an economy. The basic task of any banking organization is it to mobilize savings from the investors’ community and channel these savings to high - yielding projects. The fundamentals of most banks in the world are based on interest charged on loans and interest paid on deposits. Islamic banking is based on Islam’s Shariah principles, according to those principles, interest (Ribah) in any form is unlawful and a borrower must not bear all the risks/ cost of a failure, resulting in a balanced distribution of income and not allowing the lender to monopolize the economy. Hence, Islamic Banking operates without charging or paying interest. India is still in the front line for attracting placements and investments from abroad, and the Muslim dominated Middle East countries are having excess funds and are looking for suitable investment opportunities; this is the precise time to understand and adopt this emerging mode of banking known as Islamic Banking and to analyze its prospects in India. However, the present rules and regulations prohibit this banking system from entering and setting base in India. The authors have suggested a universally accepted legal frame work for introducing the same in India, after research on the past, present and existing regulatory models and market scenario.